THE EPIC OF MANAS AS AN ARCHETYPE OF IMMORTAL CONSCIOUSNESS AND A FORM OF NOETIC THINKING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
From a philosophical standpoint, the Manas epic can be regarded as a kind of metaphysical “code” that embodies the idea of eternity, spiritual transcendence, and the synchronization of the human being with cosmic rhythms. Manas-Aykȫle (the Magnanimous) symbolizes a state of inner harmony, where heroism is not reduced to mere physical strength but emerges as an expression of spiritual service and the readiness to act in accordance with the cosmic order. Aykȫle Manas emerges as a symbol of the eternal cosmic spirit, an embodiment of the power that elevates humanity above transient passions and earthly concerns. His essence lies not in chronology or material deeds, but in the sacred energy that connects the human realm with the celestial order. This, indeed, constitutes the true greatness of the ‘Manas’ epic: it is not merely a narrative about a heroic figure, but a philosophical model of infinity and spiritual transcendence over the finitude of the material world. Moreover, the epic can be interpreted as a form of “collective nooetic thinking,” in which the hero’s persona becomes a symbol not only of national self-awareness but also of a universal human ideal striving toward higher values and spiritual synthesis. Manas is not an earthly “titan,” but rather a “pillar between Heaven and Earth,” a figure that maintains the balance between chaos and harmony,history and eternity.
Keywords: Manasness, Archetype, Nooethics, Post-myphological Conscienceness, Manasian Ethics, Realm of Kayyp, Universal Ascension, Transhumanitarian Ethical Thought, Homo Noosphericus.